Sugar-sweetened beverage consumption among Indigenous Australian children aged 0-3 years and association with sociodemographic, life circumstances and health factors - Thurber, Katherine A; Long, Johanna; Salmon, Minette; Cuevas, Adolfo G; Lovett, Raymond (My University, 2019)
To explore beverage intake and associations between sugar-sweetened beverage (SSB) intake and sociodemographic, life circumstances, health and well-being factors in a national cohort of Indigenous children. We calculated prevalence ratios for any SSB consumption across exposures, using multilevel Poisson regression (robust variance), adjusted for age group and remoteness. A key informant focus group contextualised these exploratory findings. Diverse settings across Australia. Families of Indigenous children aged 0-3 years, in the Longitudinal Study of Indigenous Children. Half (50·7 %, n 473/933) of children had ever consumed SSB at survey, increasing from 29·3 % of 0-12-month-olds to 65·7 % of 18-36-month-olds. SSB consumption prevalence was significantly lower in urban and regional v. remote areas, and in families experiencing socio-economic advantage (area-level advantage, caregiver employed, financial security), better life circumstances (caregiver social support, limited exposure to stressors) and caregiver well-being (non-smoking, social and emotional well-being, physical health). SSB consumption prevalence was significantly lower among those engaged with health services (adequate health-service access, regular prenatal check-ups), except SSB consumption prevalence was higher among those who received home visits from an Aboriginal Health Worker compared with no home visits. Key informants highlighted the role of water quality/safety on SSB consumption. A substantial proportion of Indigenous children in this sample consumed SSB from an early age. Health provider information needs to be relevant to the context of families' lives. Health system strategies must be paired with upstream strategies, such as holistic support programmes for families, reducing racism and improving water quality.
Public Health Nutrition
Keywords: Childhood and child development; Health and wellbeing